Structure‐based design, synthesis and biological evaluation of a NAD+ analogue targeting Pseudomonas aeruginosa NAD kinase. (8th September 2022) - Rahimova, Rahila; Nogaret, Pauline; Huteau, Valérie; Gelin, Muriel; Clément, David A.; Labesse, Gilles; Pochet, Sylvie; Blanc‐Potard, Anne‐Béatrice; Lionne, Corinne
Abstract : Multidrug resistance is a major public health problem that requires the urgent development of new antibiotics and therefore the identification of novel bacterial targets. The activity of nicotinamide adenine dinucleotide kinase, NADK, is essential in all bacteria tested so far, including many human pathogens that display antibiotic resistance leading to the failure of current treatments. Inhibiting NADK is therefore a promising and innovative antibacterial strategy since there is currently no drug on the market targeting this enzyme. Through a fragment‐based drug design approach, we have recently developed a NAD + ‐competitive inhibitor of NADKs, which displayed in vivo activity against Staphylococcus aureus . Here, we show that this compound, a di‐adenosine derivative, is inactive against the NADK enzyme from the Gram‐negative bacteria Pseudomonas aeruginosa (PaNADK). This lack of activity can be explained by the crystal structure of PaNADK, which was determined in complex with NADP + in this study. Structural analysis led us to design and synthesize a benzamide adenine dinucleoside analogue, active against PaNADK. This novel compound efficiently inhibited PaNADK enzymatic activity in vitro with a K i of 4.6 μm . Moreover, this compound reduced P. aeruginosa infection in vivo in a zebrafish model. Abstract : The previously synthesized di‐adenosine derivative NKI1 inhibits S. aureus NADK but not P. aeruginosa NADK. P. aeruginosa NADK crystal structure explains the lack of effect of NKI1. A new rationally designed NAD + analogue containing a benzamide inhibits P. aeruginosa NADK. This compound displays activity against P. aeruginosa in a zebrafish infection model.